Genetics of Schizophrenia and other Psychotic Disorders - Pepper, Edward; G. Cardno, Alastair (Current Psychiatry Reviews, 2014)
Research into the genetic basis of schizophrenia is advancing rapidly. This review gives a broad overview of results from successive phases of studies in this field, linking these with recent findings and likely future research directions. Among recent findings, large-scale epidemiological studies based on Scandinavian population registers, have provided further evidence of substantial heritability and evidence that a wide range of psychotic and non-psychotic disorders partly share genetic risk factors with schizophrenia. In molecular genetics, large collaborative genomewide association studies (GWAS) are providing evidence of common risk variants, each of small effect, and many more variants are likely to be found as samples sizes increase further. A range of rarer chromosomal copy number variants (CNVs) have been associated with schizophrenia, and both GWAS and CNV studies have provided molecular evidence of genetic overlap between schizophrenia and other disorders. There is increasing interest in phenotypes beyond diagnosis, including further clinical variables and endophenotypes. Next-generation sequencing studies are beginning, with the potential for fast, inexpensive sequencing of the whole genome in large samples, and there is an increasing focus on the functional effects of the candidate risk variants that are being identified.
Keywords: schizophrenia